2018
DOI: 10.29060/taps.2018-3-2/oa1041
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of interprofessional education across 13 healthcare professions in Japan

Abstract: Background: With the rapid aging of the population, collaboration among the various medical professions throughout the country is becoming increasingly indispensable in Japan. To promote collaboration in medical care, it is necessary to introduce the c oncept of collaboration to students at an early stage of their professional education. Despite this need, there are no core medical, healthcare and welfare education curricula in Japan that include interprofessional education (IPE). Therefore, the status of IPE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…IPC requires that mutual professionals learn expected roles with, from and about each other through prolonged interprofessional communication across many years. Based on their prerequisite education, it is likely that young healthcare professionals may regard superficial sharing of information as IPC,31 32 suggesting that younger healthcare professionals may tend to think that they conduct better IPC than older healthcare professionals. Younger professionals who are motivated to collaborate more within and across organisations may play a critical role in IPC.…”
Section: Discussionmentioning
confidence: 99%
“…IPC requires that mutual professionals learn expected roles with, from and about each other through prolonged interprofessional communication across many years. Based on their prerequisite education, it is likely that young healthcare professionals may regard superficial sharing of information as IPC,31 32 suggesting that younger healthcare professionals may tend to think that they conduct better IPC than older healthcare professionals. Younger professionals who are motivated to collaborate more within and across organisations may play a critical role in IPC.…”
Section: Discussionmentioning
confidence: 99%
“…Lectures were the most common learning strategy adopted for IPE. A previous Japanese study reported that approximately half of IPE programs were delivered through lectures [16]. However, in our study, one-third of IPE programs used didactic lectures without interaction between multi-professional students.…”
Section: Discussionmentioning
confidence: 62%
“…The survey yielded a high response rate of 79.0%. Response rates in previous studies were low [15, 16]. Previous studies targeted a wide range of medical and healthcare and social professions, and did not have strategies for reminding schools that had not responded to their questionnaires.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations